1995
DOI: 10.1207/s15327752jpa6503_1
|View full text |Cite
|
Sign up to set email alerts
|

MMPI-2 Clinical Correlates for Ten Common Codes

Abstract: A number of researchers have called for the establishment of a Minnesota Multiphasic Personality Inventory-2 (MMPI-2; Butcher, Dahlstrom, Graham, Tellegen, & Kaemmer, 1989) correlate literature that is based directly on investigations of the revised MMPI. The purpose of this study was to examine clinical correlates found for 9 commonly occurring 2-point codes, each of which contained a minimum of 20 patients, and for 82 profiles that were within-normal-limit (WNL) in a sample of 289 female and 308 male psychia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
18
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 11 publications
5
18
0
Order By: Relevance
“…To address this issue, Graham, Ben-Porath, and McNulty (1999) provided a sourcebook on MMPI-2 correlates for an outpatient mental health setting and demonstrated that MMPI-2 scores produced by these outpatients mirrored the prevalent psychopathology found among them (e.g., depression and anxiety) and that the correlates of most scales and code types were similar to those reported previously for other settings. Moreover, two recent studies on MMPI-2 code types Archer, Griffin, & Aiduk, 1995) have found that the correlates of code types of psychiatric inpatients were remarkably similar to those reported decades earlier.…”
Section: Private Practice Tucker Georgiasupporting
confidence: 78%
“…To address this issue, Graham, Ben-Porath, and McNulty (1999) provided a sourcebook on MMPI-2 correlates for an outpatient mental health setting and demonstrated that MMPI-2 scores produced by these outpatients mirrored the prevalent psychopathology found among them (e.g., depression and anxiety) and that the correlates of most scales and code types were similar to those reported previously for other settings. Moreover, two recent studies on MMPI-2 code types Archer, Griffin, & Aiduk, 1995) have found that the correlates of code types of psychiatric inpatients were remarkably similar to those reported decades earlier.…”
Section: Private Practice Tucker Georgiasupporting
confidence: 78%
“…The BPRS (Overall & Gorham, 1988) was completed within 72 hours of hospital admission by a licensed clinical psychologist or psychiatrist. These data were originally published in a study of MMPI-2 two-point code types (Archer et al, 1995) and most recently used in a study on the RC scales by Handel and Archer (in press). 1 Initial participants were excluded based on the following MMPI-2 criteria: Cannot Say responses greater than 29, Variable Response Inconsistency or True Response Inconsistency T-scores greater than 79, an Infrequency-Psychopathology T-score greater than 99, or an Infrequency raw score greater than 30.…”
Section: Methodsmentioning
confidence: 99%
“…Archer, Griffin, and Aiduk (1995) previously described this sample as employed in a study of MMPI-2 codetype correlates. After the elimination of invalid MMPI-2 protocols, the participants in the current study were reduced to a final sample of 461 (219 men and 242 women).…”
Section: Participantsmentioning
confidence: 99%